Formative research on parenting practices and community support for early childhood development among caregivers in Telangana - Chary, Janani S.; Gafurjiwala, Seema M.; Nagapurkar, Srinath; Kannuri, Nanda Kishore; Shukla, Rajan; Singh, Samiksha (International Journal Of Community Medicine And Public Health, 2023)
Background: Early Childhood Development refers to the overall development of children from conception until 5 years of age across various domains such as physical, emotional, social and cognitive development. Empowering caregivers by providing information regarding ECD and early stimulation, play and communication activities from birth will help ensure all-round child development and reduce risk of developmental delays. Methods: A cross-sectional mixed methods study was conducted in May-July 2022 in two districts of Telangana, India. A semi-structured questionnaire was administered to assess KAP among 218 primary caregivers of children aged 0 to 5 years. Two focused group discussions among secondary caregivers and 18 In-Depth Interviews among frontline workers (AWWs and ASHAs) were conducted to study about current ECD practices, sources of information and communication channels. Results: More than 80% parents had good knowledge regarding brain development, but 15 to 25% did not know that activities like talking or playing with their child could improve intelligence. Less than 50% parents associated routine activities like telling stories, being sensitive to the child, playing and protecting the child with their child’s cognitive or emotional development. Even though fathers engaged their children in play and learning activities, most felt the mother was the primary caregiver. Most participants received information regarding Health and Nutrition from Anganwadi workers, but topics like sanitation, child rearing and early stimulation were not regularly covered. Conclusions: Empowering caregivers on early learning and stimulation activities by frontline workers is crucial for ensuring overall growth and development of children into productive adults.